HSP90-Mediates Liraglutide Preconditioning-Induced Cardioprotection by Inhibiting C5a and NF-κB. Issue 5 (4th May 2022) - He, Shi-Tao; Wang, Dong-Xiao; Meng, Jian-Jun; Cheng, Xiao-Fang; Bi, Qi; Zhong, Guo-Qiang; Tu, Rong-Hui
Abstract: Objective: We previously showed that HSP90 is involved in postconditioning cardioprotection by inhibiting complement C5a. Here, we investigated whether HSP90-mediated C5a/NF-κB inhibition is responsible for the cardioprotection conferred by liraglutide. Methods: Rat hearts underwent a 30 min occlusion of the anterior descending coronary artery, after which reperfusion was performed for 2 h. A total of 100 rats were randomly assigned to the following groups: ischemia/reperfusion (I/R), sham, liraglutide preconditioning (LP, liraglutide, 0.18 mg/kg, intravenously, 12 h before ischemia), HSP90 inhibitor geldanamycin (GA, 1 mg/kg, intraperitoneally, 30 min before ischemia) plus LP, and C5a receptor antagonist PMX53 (1 mg/kg, intravenously, 30 min before ischemia) plus LP. Cardiac injury, C5a/NF-κB activation, and inflammation were investigated. Results: LP significantly attenuated I/R-induced cardiomyocyte apoptosis, infarct size, and secretion of creatine kinase-MB, lactate dehydrogenase and cardiac troponin I. These effects were complemented by decreased C5a levels, nuclear factor (NF)-κB signaling, inflammatory cytokine expression, and increased HSP90 levels. GA, an HSP90 inhibitor, promotes C5a activation, NF-κB signaling, and inflammation and suppresses cardioprotection by LP. By contrast, PMX53, a C5a inhibitor, suppressed C5a activation, NF-κB signaling, and inflammation, and enhanced cardioprotection by LP. Conclusion: HSP90 markedly contributes to LP cardioprotection by inhibiting inflammatory responsesand C5a/NF-κB signaling, ultimately attenuating I/R-induced cardiomyocyte apoptosis by suppressing the proapoptotic factor Bax, and inducing the anti-apoptotic factor Bcl2.